Lung congestion in chronic heart failure: haemodynamic, clinical, and prognostic implications - Melenovsky, Vojtech; Andersen, Mads J; Andress, Krystof; Reddy, Yogesh N; Borlaug, Barry A (European journal of heart failure, 2015)
AIMS: The goal of the study was to examine the prognostic impact, haemodynamic and clinical features associated with lung congestion in patients with chronic heart failure (HF). METHODS AND RESULTS: HF patients (n = 186) and HF-free controls (n = 21) underwent right heart catheterization, echocardiography, pulmonary function testing and chest radiography that was blindly scored for the presence and severity of lung oedema. Lung congestion correlated directly with pulmonary vascular resistance (PVR, P = 0.004) and inversely with pulmonary artery (PA) compliance (P < 0.001) and the diffusion limit for carbon monoxide (DLCO , P = 0.009). Compared with dry lung HF, wet lung HF patients (congestion score > median) had 25% lower PA compliance and 25-35% higher PVR, transpulmonary gradients and PA pressures (40 vs. 32 mmHg, P < 0.001) despite marginally higher PA wedge pressure (PAWP; 22 vs. 19 mmHg, P = 0.002). Wet lung HF patients displayed more right ventricular (RV) dilatation and dysfunction, more restrictive ventilation and greater reduction of DLCO . The strongest correlates of lung congestion were NT-proBNP, haemoglobin, albumin, and glomerular filtration, all surpassing PAWP. After a median of 333 days (interquartile range 80-875), 59 patients (32%) died. Lung congestion was associated with reduced survival (P < 0.0001), even after adjusting for PAWP, NT-proBNP, anaemia, CAD and renal dysfunction. CONCLUSION: Interstitial lung oedema is associated with pulmonary vascular disease, RV overload and dysfunction and increased mortality in HF. These data reinforce the importance of aggressive decongestion in HF and suggest that novel agents aimed at reducing lung water may help to deter progression of pulmonary vascular disease and biventricular HF.
Keywords: echokardiografie; Congestion; Statistics as Topic; Ventricular Dysfunction, Right; Female; Pulmonary oedema; Lung; radiografie; Radiography; statistika jako téma; Hypertension, Pulmonary; ženské pohlaví; plicní edém; Cardiac Catheterization; Heart Failure; lidé; srdeční selhání; Survival Analysis; Vascular Resistance; Pulmonary Edema; Echocardiography; stupeň závažnosti nemoci; prognóza; Right heart; cévní rezistence; Risk Factors; retrospektivní studie; Spojené státy americké; Male; Aged; Pulmonary vascular resistance; rizikové faktory; dysfunkce pravé srdeční komory; Prognosis; analýza přežití; plíce; plicní hypertenze; srdeční katetrizace; United States; Heart failure; lidé středního věku; Respiratory Function Tests; senioři; mužské pohlaví; respirační funkční testy; Severity of Illness Index; Haemodynamics; Retrospective Studies; Middle Aged; Humans